The Comparison between the Works of Machine Translation and Human Translator in Translating Indonesian Short Story into English - Setiyono, Junaedi (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
In this digital era, translators cannot ignore the advantages of using machine translation. This research aims to compare the translation works carried out by machine translation with human translator in translating Indonesian short story into English. In comparing, the researcher focuses on the finite changes between machine translation and human translator. The research method used is descriptive-qualitative method proposed by Enio Cipani and comparative study by Robert L Stake. Meanwhile, for the finite changes, the researcher uses Jim Miller's theory of finite and non-finite clauses. Related to the data, he chooses one of the short stories on the page of Dalang Publishing, a publisher based in San Mateo, California, United States, namely Han Gagas’ short story Pekik Burung Kedasi di Tepi Kahayan which was translated by Umar Thamrin becoming Crying Cuckoos over the Kahayan. The findings of this research are that the Indonesian short story which originally had 2844 words after being translated into English by a translation machine, i.e.  Google Translate, became 3487 words. Meanwhile, a human translator translated it into 3210 words. Regarding sentences, the sentences in the Indonesian short story, whose total number is 241 sentences, after being translated by the machine translation became 242 sentences. Meanwhile, the human translator translated it 254 sentences. Focusing on the finite, 297 fundamental changes were found in the works of machine translation compared with human translator (including the changes of nouns, adjectives, etc.). Moreover, among those changes, there were 213 finite changes. It means that 71.72% of finites in the text translated by machine translation underwent the finite changes. Thus, it can be concluded that concerning the sense of sentences, the work of machine translation was quite different from the human translator in translating a short story from Indonesian into English.